A Rare Central Venous Catheter Malposition in a 10-Year-Old Girl. (23rd January 2018) - Movafegh, Ali; Saliminia, Alireza; Atef-Yekta, Reza; Azimaraghi, Omid
Abstract : Central venous catheters (CVCs) are placed in operating rooms worldwide via different approaches. Like any other medical procedure, CVC placement can cause a variety of complications. We report the case of an unexpected malposition of a catheter in the right internal jugular vein, where it looped back on itself during placement and went upward into the right internal jugular vein. CVC line placement should always be viewed as a procedure that could become complicated, even in the hands of the most experienced operators.